Digital Innovation Capability in MSME Information Systems and Its Impact on Digital Service Quality and Consumer Loyalty in Indonesia - Hardini, Inkreswari Retno; Fadlullah, Fauzan; Shabrina, Fildzah; Atmadja, Ferry Setyadi (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2026)
This research looks at the digital innovation capability as part of the structural element of the Micro, Small, and Medium Enterprise (MSME) information systems and its impacts on the quality of digital services and consumer loyalty in the Indonesian Smart Economy environment. Digital innovation is theorized as the system-level potential, which entails the alignment of online ordering frameworks, online payment gateways, platform interoperability, and responsiveness of online services to MSME digital platforms. This study is partaking that instead of digitalization being a marketing program, digitalization is an information systems capability within operational architecture. The quantitative survey methodology was used in this study, where 50 consumers that had completed transactions with technology-based MSMEs participated in the survey. The relationship between digital innovation capability and consumer loyalty was assessed by simple linear regression analysis. The results show that the impact of digital innovation capability on loyalty behavior is highly significant (R² = 0.536, p < 0.05) and that it explains 53.6 percent of the loyalty behavior. These findings indicate that improved system integration leads to perceived quality of digital service, which subsequently intensifies user retention and repeat purchase intentions. This study contributes to information systems research by empirically validating digital innovation capability as a measurable construct in MSME digital platforms and by supporting the development of capability-based digital transformation models within emerging digital ecosystems.